XVI. The Impact of the Development Level of Digital Economy on the Export Trade Between China and Countries Along the “Belt and Road - Zhang, Zhongyun; Liu, Dazhi (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
As an emerging economic form supported by new technologies, the development of the digital economy is changing the global economic pattern. It profoundly impacts the market pattern of international trade and the production organisation structure. Institutions and scholars also have different opinions on measuring digital economy development indicators. Much research is on the development of global trade in the digital economy. At present, the main research directions of the academic circle are the impact mechanism of the digital economy on international trade, the heterogeneous impact of the digital economy on the trade of different countries, and the impact on trade with other countries. This paper mainly studies the current situation and existing problems of the development of the digital economy, analyses the impact of the digital economy on China's export trade with countries along the "Belt and Road" through theoretical knowledge, and puts forward future policy suggestions based on the impact.